An Examination of Motivation and Routine Activity Theory to Account for Cyberattacks Against Dutch Web Sites - Holt, Thomas J. (Criminal justice and behavior, 2020)
This study provides a partial test of the relationship between actor motivations and target suitability using a routine activity framework to understand a form of cybercrime called web defacements. Specifically, the relationships between the visibility, inertia, value, and accessibility of the target in online spaces relative to the unique nonmonetary motivations of the attacker were examined. This study utilized a sample of 138,361 web defacements performed against websites hosted within the Netherlands IP space from January 2011 to April 2017. Seven multinomial logistic regression models were conducted for each self-identified motive for the attack, clustered by attacker to minimize the size of standard errors. The findings demonstrated partial support for aspects of routine activity theory to account for differences in offender motivation, suggesting web defacements are similar to other forms of cybercrime. At the same time, motivations differentially shape target selection.